Knowledge and Practice Regarding Pressure Injury Prevention among Nurses at King Abdul-Aziz Specialist Hospital - Afnan Sahrah; Wafaa Althobaiti; Sahar Albalawi; Ensherah Althobiti; Turki Alfattah; Abdulellah Almalki; Ahlam Alotaibi; Maha Alkhaldi; Talal Alqurashi; Faten Sahrah; Munirah Alfifi; Rami Alnemari; et al. (Evidence-Based Nursing Research)
Context: Preventing hospital-acquired pressure injuries (HAPI) poses a significant challenge within tertiary service hospitals. These skin lesions cause discomfort and elevate the risk of severe infections, leading to increased healthcare costs and a high mortality rate due to sepsis. Thus, prevention requires an interdisciplinary approach to care.